Wabah dalam Perspektif Kristen dan Islam (Studi Alkitab dan Al Qur’an sebagai Kitab Suci) - Mercusuarridha, Mercusuarridha; HS, Moh. Nuh (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The phenomenon of the Covid-19 disease outbreak raises various speculations and questions, especially how the correlation between the disease outbreak and religion. This research is a literature research that aims to explain the conception of the plague in the perspective of Christianity and Islam through the study of the Bible and the Qur'an, with a descriptive analysis method. The results of this research, first, the plague is a form of punishment from God. Second, the plague is a